Impacts of continuous cropping on soil fertility, microbial communities, and crop growth under different tobacco varieties in a field study - Hao Xia; Chaoqiang Jiang; Muhammad Riaz; Fei Yu; Qing Dong; Yifeng Yan; Chaolong Zu; Chuyue Zhou; Jitao Wang; Jia Shen (Environmental Sciences Europe)
Abstract Continuous cropping obstacles are significant factors that limit the yield and quality of tobacco. Thus, the selection and breeding of varieties is a crucial strategy for mitigating these challenges. However, the effects and mechanisms by which different tobacco varieties influence the structural composition of soil microbial remain unclear. To address this, we conducted a field experiment involving five tobacco varieties (K326, K394, XL, Y87, and Y97) and two types of soil (continuous cropping obstacle soil and normal soil). We examined microbial responses to different tobacco varieties in each soil type. Our results revealed that soil available nutrients and organic matter were decreased in obstacle soil compared to normal soil. The fresh biomass decreased by 18.05–27.92% in obstacle soil (except K394 and Y97). The microbial community composition in the rhizosphere soil remained consistent in various tobacco varieties in obstacle soil. The connections between soil fertility nutrients and microbial communities were reduced in obstacle soil compared to normal soil. The alteration of bacterial community composition was a stochastic process, whereas the modification of fungal community composition was a deterministic process in obstacle soil. Furthermore, the abundance of differential fungi (Zoopagomycota) was notably higher in obstacle soil. Overall, our results revealed that the disturbance of microbial communities and soil degradation in the obstacle soil are primary factors contributing to reduced crop yields. Therefore, it is an economical strategy for overcoming continuous cropping obstacles by utilizing rhizosphere microecology through multi-variety planting.